Recent development in studies of alternative jet fuel combustion: Progress, challenges, and opportunities. (February 2016) - Zhang, Chi; Hui, Xin; Lin, Yuzhen; Sung, Chih-Jen
Abstract: With the growing air transport demand and concerns about its environmental impacts, alternative jet fuels derived from non-conventional sources have become an important strategy for achieving a sustainable and green aviation. In the past 10 years, governments around the world along with aviation industry have invested significant efforts into exploring all sorts of alternative jet fuels that can be used to power aircraft engines. Among all the alternative jet fuels explored, the aviation sector has agreed that hydrocarbon-based 'drop-in' replacement fuels, which are fully interchangeable and compatible with current conventional jet fuels, would be the best choice in the near future, as they can be used without any modifications to today׳s aircraft or fuel infrastructure. This paper reviews the current state of development of 'drop-in' alternative jet fuels including various Fisher–Tropsch synthetic jet fuels and bio-jet fuels. Recent advances in research activities on alternative jet fuels, including fuel property evaluations, combustor component tests, engine tests, and flight tests, are highlighted. Furthermore, basic research needs for understanding the combustion characteristics of alternative jet fuels are underlined and discussed by reviewing recent fundamental combustion studies on ignition, extinction, flame propagation, emissions, and species evolution of various conventional and alternative jet fuels. Recognizing that the use of 'simpler' surrogate fuels to emulate the behavior of 'complex' alternative jet fuels is of fundamental and practical importance for the development of physics-based models to enable quantitative emissions and performance predictions using combustion modeling, recent studies on surrogate formulation for alternative jet fuels are also reviewed and discussed. This review concludes with a brief discussion of future research directions.